Monthly dynamics of phytoplanktonic assimilatory pigments in the Romanian Black Sea coastal waters between Constanta and Agigea during 1977 - Bologa, Alexandru S. (Cercetări Marine - Recherches Marines, 2026)
The amounts of phytoplanktonic assimilatory pigments from the area less influenced by the Danube of the Romanian Black Sea coastal waters were recorded every month (at Constanta) and every ten days (at Agigea.) in order to follow the quantitative dynamics of phytoplankton and its blooms during 1977.